2007
DOI: 10.1016/j.neulet.2007.02.049
|View full text |Cite
|
Sign up to set email alerts
|

CART peptides increase 5-hydroxytryptamine in the dorsal raphe and nucleus accumbens of freely behaving rats

Abstract: Cocaine and amphetamine-regulated transcript peptides (CART) are implicated in the antidepressant effect. This may involve in 5-hydroxytryptamine (5-HT) in the CNS. The aim of the present studies was to investigate the effect of CART peptides on extracellular 5-HT in the dorsal raphe nucleus (DRN) and nucleus accumbens (NAcc) using a microdialysis approach in freely-behaving rats. Reverse infusion of CART in the DRN produced a concentration (10 µM-100 µM) -dependent increase in 5-HT in the DRN. Similarly, CAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The notion that CART may play a role in the pathogenesis of major depression is further corroborated by the fact that it can modulate signal transduction pathways of neurotrophic factors such as brain-derived neurotrophic factor, and directly control the expression of genes coding for key enzymes in the biosynthesis of serotonin, factors all assumed to be involved in depression (for reviews see: Ma et al, 2007;Pae et al, 2007;Rogge et al, 2008). More specifically, CART markedly enhances hypothalamic and cortical serotonin release in the rat (Vaarmann and Kask, 2001), but the neuronal circuitry underpinning this phenomenon is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that CART may play a role in the pathogenesis of major depression is further corroborated by the fact that it can modulate signal transduction pathways of neurotrophic factors such as brain-derived neurotrophic factor, and directly control the expression of genes coding for key enzymes in the biosynthesis of serotonin, factors all assumed to be involved in depression (for reviews see: Ma et al, 2007;Pae et al, 2007;Rogge et al, 2008). More specifically, CART markedly enhances hypothalamic and cortical serotonin release in the rat (Vaarmann and Kask, 2001), but the neuronal circuitry underpinning this phenomenon is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Pae et al (2007) commented on the therapeutic usefulness of CART in the treatment of depression. In recent years, Ma et al (2007) observed that increased the extracellular 5-HT, and speculated that the effect may be responsible for antidepressant-like action of CART. Furthermore, CART influences the expression of a range of neurotransmitters such as g-aminobutyric acid, 5-HT, noradrenaline (NA), and dopamine that directly regulate affective disorders including depression Figure 3 Photomicrographs showing cocaine-and amphetamine-regulated transcript peptide immunoreactive (CART-ir) cells (arrows) and fibers (arrowheads) in the hypothalamic paraventricular nucleus (PVN) of shamoperated (sham, (a)), olfactory bulbectomy (OBX, (b)), group housed (paired, (c)), and social isolated for 6 weeks (socially isolated, (d)) rats.…”
Section: Effect Of Icv and Intra-cea Administration Of Cart On Depresmentioning
confidence: 99%
“…Scale bar ¼ 200 mm. (Vaarmann and Kask, 2001;Choi et al, 2003;Yang et al, 2004;Hunter et al, 2006;Jaworski et al, 2007;Ma et al, 2007), and it is possible that antidepressant action of CART may be mediated via some of these neurotransmitters.…”
Section: Effect Of Icv and Intra-cea Administration Of Cart On Depresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in rats that CART may have an antidepressant effect through increases in extracellular serotonin (Ma et al 2007). Specifically, a CART infusion in the dorsal raphe nucleus leads to a significant increase of serotonin efflux in the nucleus accumbens, a major target of dorsal raphe serotonergic projections.…”
Section: Cart and Serotoninmentioning
confidence: 99%